Consensus recommendations for histological criteria of autoimmune hepatitis from the International AIH Pathology Group: Results of a workshop on AIH histology hosted by the European Reference Network on Hepatological Diseases and the European Society of Pathology. (12th March 2022) - Lohse, Ansgar W.; Sebode, Marcial; Bhathal, Prithi S.; Clouston, Andrew D.; Dienes, Hans P.; Jain, Dhanpat; Gouw, Annette S. H.; Guindi, Maha; Kakar, Sanjay; Kleiner, David E.; Krech, Till; Lackner, Carolin; et al.
Abstract: Background & Aims: Diagnostic histological criteria for autoimmune hepatitis (AIH) have not been clearly established. Previously published criteria focused mainly on chronic AIH, in which inflammatory changes mainly occur in portal/periportal regions and may not be applicable to acute presentation of AIH, in which inflammatory changes are typically predominantly lobular in location. International consensus criteria for the diagnosis and assessment of disease severity in both acute and chronic AIH are thus urgently needed. Methods: Seventeen expert liver pathologists convened at an international workshop and subsequently used a modified Delphi panel approach to establish consensus criteria for the histopathological diagnosis of AIH. Results: The consensus view is that liver biopsy should remain standard for diagnosing AIH. AIH is considered likely, if there is a predominantly portal lymphoplasmacytic hepatitis with more than mild interface activity and/or more than mild lobular hepatitis in the absence of histological features suggestive of another liver disease. AIH is also considered likely if there is predominantly lobular hepatitis with or without centrilobular necroinflammation and at least one of the following features: portal lymphoplasmacytic hepatitis, interface hepatitis or portal‐based fibrosis, in the absence of histological features suggestive of another liver disease. Emperipolesis and hepatocellular rosettes are not regarded as being specific for AIH. Conclusions: The criteria proposed in this consensus statement provide a uniform approach to the histological diagnosis of AIH, which is relevant for patients with an acute as well as a chronic presentation and to more accurately reflect the current understanding of liver pathology in AIH.